Antecedents of Perceived Fairness in Criminal Courts: A Comparative Analysis. Issue 3 (2nd July 2020) - Alda, Erik; Bennett, Richard; Marion, Nancy; Morabito, Melissa; Baxter, Sandra
ABSTRACT: Criminal courts are an essential component of the criminal justice system. How people perceive courts determines, in part, their compliance with court decisions. When courts are perceived as being just, fair and trustworthy, citizens are more likely to respect court rulings. However, few people have direct experience with the criminal courts, but many do with the police. This paper explores whether citizens' perception of police fairness affects their perception of criminal courts as being fair and examines the influences of a variety of individual and community factors upon this relationship. We tested a conceptual model with three clusters of predictive variables (individual, community, and national levels) based on data from the Caribbean. The findings indicate that perceived fairness of courts is driven primarily by perceived fairness of the police as well as by involvement in one's community and an individual's crime victimization. Policy implications of these findings are explored.